UPAYA MEMBANGUN PROFESIONALISME GURU PENDIDIKAN DASAR DALAM ERA GLOBALISASI MELALUI KEMITRAAN SEKOLAH - Hastuti, Sri (Jurnal Pendidikan Ilmu Sosial, 2018)
This paper aims to convey ideas on how to construct professionalism of Secondary Education teachers in the global era through school partnership programs. The advancement of education can be demonstrated by educators in schools through their teaching process who still do subject matter centered, but who are expected to have to do a community life centered. The author conducts information gathering and opinions as a means of resolving and understanding the importance of a school partnership to build the quality of education at school. Partnership Schools play a very important role in the development of quality education in schools, where teachers in schools are expected to know the environmental conditions of students; school principals and teachers are expected to be able to utilize existing resources in the community/public; schools must work with organizations and agencies that have important tasks for students. Increasing teacher professionalism in schools to improve education quality.